Spinal muscle activity during different rugby scrum engagement procedures - Cazzola, D.; Stone, B.; Holsgrove, T. P.; Trewartha, G.; Preatoni, E. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Biomechanical studies of rugby union scrummaging have focussed on kinetic and kinematic analyses, whilst muscle activation strategies employed by front row players during scrummaging are still unknown. The aim of this study was to investigate the activity of the sternocleidomastoid, upper trapezius and erector spinae muscles during machine and live scrums. Nine male front-row forwards scrummaged individually against a scrum machine under "crouch-touch-set? and "crouch-bind-set? conditions, and against a two-player opposition in a simulated live condition. Results suggest that the pre-bind technique, may effectively prepare the cervical spine by stiffening joints before the impact phase. Additionally, machine scrummaging does not replicate the muscular demands of live scrummaging for the erector spinae.